A comparative evaluation of in vitro antihyperglycemic potential of Bamboo seed rice (Bambusa arundinacea) and Garudan samba (Oryza sativa): An integrated metabolomics, enzymatic and molecular docking approach. (May 2021) - Haldipur, Ashrita C.; Srividya, N.
Abstract: The study reports the in vitro antihyperglycemic potential of Bamboo seed rice/BSR, a brown rice from Bambusa arundinacea species in comparison to a traditional Indian brown rice - Garudan samba/GS from Oryza sativa species using an integrated approach. Untargeted phenolic profiling using Q-TOF-LC-MS/MS confirmed sixty-three phenolic metabolites in BSR and thirty-nine in GS. The most abundant phenolics in BSR and GS were gallic acid, 4-hydroxybenzaldehyde, caffeic acid 4-O-glucoside and p -coumaric acid. Additionally, eriocitrin was abundant in BSR and cirsimaritin in GS. Predicted glycemic index determined using an in vitro starch digestibility technique indicated BSR to be a low GI variety and GS a moderate GI variety. In terms of antihyperglycemic enzyme inhibitory potential, BSR exhibited better α-amylase inhibition, whereas GS exhibited greater inhibition of dipeptidyl peptidase IV. This was further confirmed using molecular docking techniques which revealed that eriocitrin and cirsimaritin were strong inhibitors of α-amylase and DPP IV enzymes. The study thus revealed brown rice varieties from both Bambusa sp. and Oryza sp. as healthier options to white rice in the dietary management of diabetes and as good sources of several bioactive phenolic compounds. Graphical abstract: Image 1 Highlights: 63 phenolic metabolites were confirmed in Bamboo rice and 39 in Garudan samba. Bamboo rice exhibited low pGI and Garudan samba exhibited moderate pGI. 1st study to report DPP IV enzyme inhibition by brown rice phenolic extracts. Eriocitrin & cirsimaritin showed high amylase & DPP IV inhibition in docking studies.